CT colonography: accuracy, acceptance, safety and position in organised population screening. Issue 2 (2nd December 2014) - de Haan, Margriet C; Pickhardt, Perry J; Stoker, Jaap
Abstract : Colorectal cancer (CRC) is the second most common cancer and second most common cause of cancer-related deaths in Europe. The introduction of CRC screening programmes using stool tests and flexible sigmoidoscopy, have been shown to reduce CRC-related mortality substantially. In several European countries, population-based CRC screening programmes are ongoing or being rolled out. Stool tests like faecal occult blood testing are non-invasive and simple to perform, but are primarily designed to detect early invasive cancer. More invasive tests like colonoscopy and CT colonography (CTC) aim at accurately detecting both CRC and cancer precursors, thus providing for cancer prevention. This review focuses on the accuracy, acceptance and safety of CTC as a CRC screening technique and on the current position of CTC in organised population screening. Based on the detection characteristics and acceptability of CTC screening, it might be a viable screening test. The potential disadvantage of radiation exposure is probably overemphasised, especially with newer technology. At this time-point, it is not entirely clear whether the detection of extracolonic findings at CTC is of net benefit and is cost effective, but with responsible handling, this may be the case. Future efforts will seek to further improve the technique, refine appropriate diagnostic algorithms and study cost-effectiveness.